Investor Commitment to Responsible Investing and Firm ESG Disclosure - Isidro, H.; Dirk E. Black; Marques, A. (Accounting and Business Research 50 year Conference, 2023)
We examine whether investors’ commitment to socially responsible investment principles influence the public disclosure of environmental, social, and governance (ESG) issues of their investee firms. We find that following institutional investors’ public commitment to the United Nations Principles for Responsible Investment (PRI), ESG disclosure in SEC reports increases with the proportion of shares owned by institutional investors committed to PRI. Our evidence is robust to considering: (1) ownership by PRI investors before they signed the PRI protocol and ownership by other (non-PRI) investors, (2) current and past firm ESG performance, (3) simultaneous estimation of investment, ESG performance, and ESG disclosure, and (4) shock to investor demand of environmental information. We also find that the improvement in firm ESG disclosure is attributable primarily to PRI institutional investors from Europe and it is not driven only by large influential institutional investors. We also provide evidence that PRI investors actively influence ESG reporting of their portfolio firms through shareholder proposals that directly request additional disclosure on sustainability. Our analyses suggest that investors public commitment to social responsibility is a critical mechanism to improve firms’ public disclosure of ESG activities.